Educação ambiental e representações sociais na educação de surdos - Demamann, Sandra Teresinha (2006)
Social, cultural, political and economical aspects among others are frequently the source of environmental problems. The professionals working in education and those who are preparing to work in this field must be informed about the connection of the aspects mentioned earlier and the environmental problems. These professionals must also look for the solution of such problems, and this is the reason why we have this research project. The students of Special Education at UFSM, and also the teachers of Doctor Reinaldo Fernando Cóser Special School, are working in this project as well. Specifically, the objective is to identify the social representation of the students of the Special Education course and the connection of these students with the environmental problems. We still intend to meet the teachers are working with deaf students. We hope to identify also teacher s representation at Deaf School and their connections with environmental problems, and know the path they follow to teach about environmental problems with their students. The interpretation of some data has been done by discussion, interviews and by some predetermined questions. The biggest part of the professionals, teachers and also students, represent aspects like air, trees, water and their preservation. These representations are going to be modified to deaf people education, especially the way that society looks at these persons and the way the society sees their culture and identity.